2013
DOI: 10.1002/jez.b.22549
|View full text |Cite
|
Sign up to set email alerts
|

Development of fore‐ and hindlimb muscles in frogs: Morphogenesis, homeotic transformations, digit reduction, and the forelimb–hindlimb enigma

Abstract: Here we provide the first detailed description, based on immunohistochemistry and dissections, of the limb muscle development in the direct developing frog Eleutherodactylus coqui. We compare E. coqui with other tetrapods and discuss our results in a broad evolutionary and developmental context to address some major questions concerning the origin, evolution, and ontogeny of the tetrapod limbs. Our observations and comparisons: (1) support the "in-out" developmental mechanism of the appendicular pectoral muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
117
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(128 citation statements)
references
References 44 publications
5
117
1
5
Order By: Relevance
“…As explained in the Results section, the fact that the axial pectoral muscles are often deep girdle muscles probably explains why the levator scapulae and serratus anterior could not be seen in the pictures obtained by us of the developing muscles of axolotls from stages 46 to 54. As our ontogenetic study of frog limbs (Diogo and Ziermann, ), the present study of axolotls also supports Valasek et al's () “in–out” mechanism because at earlier ontogenetic stages the appendicular pectoral muscles start to develop far from the midline, at the level of the proximal region of the arm; only later in development they extend medially to cover a substantial part of the ventral and dorsal surfaces of the thoracic region (compare, e.g., Fig. with Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As explained in the Results section, the fact that the axial pectoral muscles are often deep girdle muscles probably explains why the levator scapulae and serratus anterior could not be seen in the pictures obtained by us of the developing muscles of axolotls from stages 46 to 54. As our ontogenetic study of frog limbs (Diogo and Ziermann, ), the present study of axolotls also supports Valasek et al's () “in–out” mechanism because at earlier ontogenetic stages the appendicular pectoral muscles start to develop far from the midline, at the level of the proximal region of the arm; only later in development they extend medially to cover a substantial part of the ventral and dorsal surfaces of the thoracic region (compare, e.g., Fig. with Fig.…”
Section: Discussionsupporting
confidence: 89%
“…However, it should be noted that a dorso‐ventral gradient was reported in Kardon's () study of the ontogeny of the hindlimb muscles of chickens. Moreover, our recent ontogenetic study of the frog Eleutherodactylus coqui (Diogo and Ziermann, ) has shown that both limbs display a proximo‐distal muscle morphogenetic gradient and that the hindlimb displays a dorso‐ventral gradient, as reported in chickens by Kardon (). Also, instead of a radio‐ulnar/tibio‐fibular gradient as seen in the regeneration and ontogeny of the musculature of both limbs of axolotls, there is mainly a ulno‐radial/fibulo‐tibial gradient in the ontogeny of the musculature of the fore‐ and hindlimbs of this frog.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Regarding the muscular anatomy of lobe-finned fishes, the major novel contributions of this work are 1) description of new muscles; 2) re-appraisal of evolutionary origin (e.g., from ventral/abductor vs. dorsal/adductor masses) and identity of previously described muscles; and 3) first comprehensive comparisons of pelvic and pectoral appendages (PELA, PECA) among these and other fish and in tetrapods, leading to proposal of new names, evolutionary origins and one-to-one homology hypotheses for all muscles of these taxa (see SI for more details, in particular between the differences between our work and previous studies). We discuss our results in the context of the anatomical, developmental, and paleontological literature, including recent papers on the soft tissues of adult dipnoans1920 and coelacanths14, of phylogenetically basal extant bony fishes such as Polypterus 21, and works on appendicular muscle development in most gnathostome clades111222232425262728293031323334.…”
mentioning
confidence: 98%